WISC-IV : advanced clinical interpretation - Weiss, Lawrence G. (Practical resources for the mental health professional., 2006)
For both experienced psychologists and graduate students, this book moves quickly through the essentials of WISC-IV interpretation and onto an insightful analysis of the major cognitive domains assessed by WISC-IV. It is the intention of the editors to raise the standard of practice from a simplistic 'test-label-place' model to a clinical model of assessing to understand and intervene. In the first chapter, the reader is presented with a comprehensive array of societal and home environment factors for which there is empirical evidence indicating their impact on the development of children's co.